Jvrisprvdentia heroica sive De jure Belgarum circa nobilitatem et insignia demonstrato in commentario ad edictum serenissimorum Belgii principum Alberti et Isabellæ emulgatum 14. decembris 1616. [....]. - Christyn, Johannes Baptista, 1622-1690; Clouwet, Peeter, 1629-1670; Danoot, Pieter, 17e eeuw; Quellinus, Erasmus, II, 1607-1678; Vivien, Balthazar, active 1662-1668 (Bruxellis : sumptibus Balthazaris Vivien [...], 1668)
Adel ten tijde van Albrecht & Isabella
Different states of the prelims of the first volume
Fouten in pagin. en katern.
Gegraveerd titelbl. E. Quellinus delineauit. P. Danoot sculpsit'
Gravures door P. Clouwet.
Teksten in Lat., Nederl. & Fr.
Keywords: Heraldry -- Law and legislation -- Belgium -- Early works to 1800.; Military religious orders; Nobility -- Belgium -- Early works to 1800.; Orders of knighthood and chivalry -- Early works to 1800.